2018
DOI: 10.1016/j.rasd.2018.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Standing balance on unsteady surfaces in children on the autism spectrum: The effects of IQ

Abstract: Background Postural stability difficulties are commonly reported in people on the autism spectrum. However, it is unclear whether unsteady surfaces may exacerbate postural stability difficulties in children and adolescents with autism spectrum disorder (ASD). Understanding balance on unsteady surfaces is important because uneven surfaces are commonly encountered in daily life. Methods Twenty-one youth on the autism spectrum and 16 youth with typical development (ages 6-16 years, IQ ≥ 79) stood on both a fixe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 42 publications
0
11
1
Order By: Relevance
“…Another possible explanation for this finding is that elevations in COP variability are more severe for individuals with ASD and comorbid intellectual disability (ID), as we only studied participants with average or above average IQs. Previous studies have shown that individuals with ASD and lower cognitive abilities show reduced postural stability relative to those with higher IQs [3,45]. While we did not see a relationship between IQ and COP variability, this may reflect the restricted IQ range of our sample (> 70).…”
Section: Feedback Guided Reactive Adjustments Of Postural Stabilitycontrasting
confidence: 75%
“…Another possible explanation for this finding is that elevations in COP variability are more severe for individuals with ASD and comorbid intellectual disability (ID), as we only studied participants with average or above average IQs. Previous studies have shown that individuals with ASD and lower cognitive abilities show reduced postural stability relative to those with higher IQs [3,45]. While we did not see a relationship between IQ and COP variability, this may reflect the restricted IQ range of our sample (> 70).…”
Section: Feedback Guided Reactive Adjustments Of Postural Stabilitycontrasting
confidence: 75%
“…Although the prevalence of balance problems in ASD is well acknowledged, explanations regarding the causes of the postural stability deficits diverge. For example, some authors outline the role of anxiety on postural instability [ 65 ] while others attribute the problem to poor cognition [ 66 ]. Nevertheless, most of the debate lies in whether postural deficits are related to sensorimotor or integrational problems.…”
Section: Discussionmentioning
confidence: 99%
“…A gymnastics is a form of systematic physical movement that can be done on the floor or on a mat in the form of a mat [4]. Children with autism will have difficulty with postural stability, especially when balance tasks present greater sensorimotor challenges on unstable surfaces [5][6] [7]. However, the pattern of motion exercises on an unstable surface using foam can improve postural control in autistic children [8].…”
Section: Introductionmentioning
confidence: 99%